Improving Prosocial Behavior Through Project-Based Learning Activities In Children Aged 5-6 Years - Alfina Hermawati; Apri Kurniasih; Retno Risti Darmawanti (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Prosocial behavior plays a crucial role in early childhood social-emotional development, as it forms the foundation for children’s ability to interact, cooperate, and demonstrate empathy in social contexts. This study aims to improve the prosocial behavior of children aged 5–6 years through the implementation of project-based learning at PAUD Budi Luhur II. The research employed a classroom action research design conducted in two cycles, involving 15 children as participants, with data collected through observation, interviews, and documentation. Data were analyzed using descriptive qualitative and quantitative techniques by comparing prosocial behavior achievement across cycles. The findings indicate a significant improvement in children’s prosocial behavior, particularly in cooperation, sharing, and helping behaviors, with 80% of children reaching the very well-developed category. These results imply that project-based learning is an effective pedagogical approach for fostering prosocial behavior in early childhood education.